The Effect Of Promotion And Quality Service On Purchase Decisions At Gramedia World Karawang - Tanti Pratiwi; Pascal Sidqi Lubis; Lulu Suwaryu; Danang Kusnanto (Primanomics : Jurnal Ekonomi & Bisnis, 2022)
The purpose of this study is to determine how much influence the promotion has on consumer purchasing decisions at the Gramedia World Bookstore, Karawang. To find out how the influence of service quality on consumer purchasing decisions at the Gramedia World Bookstore, Karawang. This study uses a quantitative method with a verification approach. The sample used in this study was 85 respondents. With the data analysis technique, the verification test was carried out with Path Analysis (path analysis) with partial hypothesis testing. The result of this research is that there is a strong and significant correlation between promotion and service quality of 0.664. There is a partial effect between Promi on purchasing decisions and service quality on purchasing decisions.